Mission-Driven and Character-Based Leadership in Local Government Tourism Management: A Qualitative Inquiry - Mutmainna, Mutmainna; Abubakar, Abubakar; Adam, Adam (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2025)
This study is motivated by indications of low work discipline and work spirit among employees of the Tourism Office of North Kolaka Regency, as reflected in late attendance, absenteeism, and frequent leave submissions. Such conditions potentially affect employee performance and the overall achievement of organizational work programs. Leadership therefore plays a crucial role in shaping employee behavior, performance, and organizational work culture. This research aims to identify the leadership style applied by the Head of the Tourism Office in managing the tourism sector, to examine its influence on employee performance and work program achievement, and to analyze its impact on organizational work culture. The study employs a qualitative descriptive approach using an inductive method. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the Head of the Tourism Office applies a character-based leadership style, characterized by exemplary behavior, discipline enforcement, continuous evaluation, and direct guidance to employees. This leadership style positively influences employee performance, supports the successful implementation of work programs, and fosters a more disciplined and responsible work culture within the organization. The study concludes that character leadership is an effective leadership approach in improving employee performance and organizational effectiveness in the public sector.